2022
DOI: 10.1111/ajt.17171
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral toxicities in pediatric solid organ transplant recipients

Abstract: Prophylaxis with valganciclovir (VGCV) is used routinely to prevent cytomegalovirus (CMV) infections in at‐risk pediatric solid organ transplant (SOT) recipients. However, the rate and factors associated with toxicities in this population are not well‐described. We conducted a retrospective cohort study of children undergoing SOT at our hospital from January 2012–June 2018. We evaluated the frequency of hematologic and renal toxicities from day 15 through 1‐year post‐SOT in relation to antiviral exposures, foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Neutropenia is frequently observed after solid-organ transplantation. It occurs in up to 30–40% of patients within the first year after transplantation [ 9 11 ]. It is mainly related to use of myelotoxic drugs such as polyclonal antibodies, mycophenolic acid, mammalian target of rapamycin inhibitors, VGCV, and trimethoprim/sulfamethoxazole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutropenia is frequently observed after solid-organ transplantation. It occurs in up to 30–40% of patients within the first year after transplantation [ 9 11 ]. It is mainly related to use of myelotoxic drugs such as polyclonal antibodies, mycophenolic acid, mammalian target of rapamycin inhibitors, VGCV, and trimethoprim/sulfamethoxazole.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study that included 572 adults who received a kidney transplant and were CMV mismatched or had a panel reactive antibody rate ≥ 80%, 208 (36.3%) participants had neutropenia that was defined as absolute neutrophil count < 1000 cells/μl. In a pediatric cohort of SOT patients, VGCV prophylaxis was associated with neutropenia [ 11 ]. In patients presenting with neutropenia, physicians are prompted to either decrease or stop VGCV, decrease or stop mycophenolic acid, stop trimethoprim/sulfamethoxazole, or use of granulocyte colony stimulating factors (G-CSF).…”
Section: Introductionmentioning
confidence: 99%
“…ValGCV, a pro‐drug of ganciclovir, is a deoxynucleoside analogue CMV DNA polymerase inhibitor indicated for the prevention of CMV disease in high‐risk pediatric kidney and heart transplant recipients when started within 10 days of SOT 1,3,4 . Primary dose‐limiting toxicities of valGCV include bone marrow suppression, including leukopenia and neutropenia and less frequently, nephrotoxicity, that is compounded by concomitant receipt of other nephrotoxic medications (e.g., calcineurin inhibitors) 4,5 …”
Section: Valganciclovir Prophylaxis Dosing CMV Dnaemia Cmv Eod N (%) ...mentioning
confidence: 99%
“…1,3,4 Primary dose-limiting toxicities of valGCV include bone marrow suppression, including leukopenia and neutropenia and less frequently, nephrotoxicity, that is compounded by concomitant receipt of other nephrotoxic medications (e.g., calcineurin inhibitors). 4,5 Despite the widespread use of valGCV as prophylaxis, there is a paucity of pediatric pharmacokinetic (PK) data to guide dosing recommendations in pSOT. The lack of a standardized strategy in all pediatric age ranges has resulted in considerable variability in valGCV dosing regimens and durations across pSOT centers, even within graft types at the same center, and suboptimal target exposures.…”
Section: One Of the Main Challenges When Considering CMV Antiviralmentioning
confidence: 99%
“…Several studies have demonstrated efficacy of ganciclovir and valganciclovir for the treatment of CMV in adult SOT recipients, and this is largely extrapolated to the pediatric SOT population ( 30 – 32 ). Hematologic toxicities such as leukopenia, neutropenia, thrombocytopenia, and anemia are well-known and reversible adverse effects of ganciclovir and valganciclovir ( 33 ). These agents are recommended to be used with caution in patients with pre-existing cytopenias, and use should be avoided when ANC < 500 cells/ml, platelet count is <25,000/ml, or hemoglobin <8 g/dl.…”
Section: Introductionmentioning
confidence: 99%